Production of Lithium-Ion Cathode Material for Automotive Batteries Using Melting Casting Process - Delin Li; Wojciech Kasprzak; Gregory S. Patience; Pierre Sauriol; Hernando Villazon Amaris; Mickael Dolle; Michel Gauthier; Steeve Rousselot; Majid Talebi-Esfandarani; Thomas Bibienne; Xueliang Sun; Yulong Liu; et al. (The Minerals, Metals and Materials Society, 2018)
In the 1990s, LiFePO4 (LFP) was discovered as a cathode material for lithium ion batteries and was successfully used in the variety of devices such as power tools, E-bikes and grid accumulators. New challenges associated with use of lithium ion batteries for automotive applications demand higher performance and operating requirements, yet these requirements need to be achieved at affordable cost and without compromising vehicle safety. The advantages of LFP as a cathode material include thermal stability, limited environmental impact and potential of low cost as compared to the cathode chemistries containing cobalt. Currently, solid state and hydrothermal processes are used to synthesize LFP at the industrial scale. However, they require multiple, time-consuming steps and costly precursors. Recently, a melting-casting process to produce LFP cathode material was investigated. The motivation behind this new process is the great flexibility of raw materials including chemical makeup and particle size, and the use of lower cost, commodity chemicals, with the benefits of increased kinetics in the molten state and energy efficiencies leading to overall process cost savings. Also, if successful this process could represent a novel application of conventional casting. Melting lithium-, iron- and phosphorus-bearing precursors in near stoichiometric ratios and casting LFP material that forms around 1000 °C requires fewer processing steps.